BKD Files Management Application - Rijois I. E. Saragih (Geviva Edukasi Trans Teknologi, 2024)
The Lecturer BKD Files Management Application is a system designed to facilitate digital management of Lecturer Tri Dharma (BKD) files. This application aims to simplify the process of recording, archiving and reporting BKD which is often complicated and time consuming if done manually. With features such as file upload, document search, and archive management, this application allows lecturers to easily manage and track various documents related to their BKD. Apart from that, this application also makes it easy for the administration to verify and monitor lecturers' BKD efficiently. The implementation of this system is expected to increase effectiveness and accuracy in BKD management, as well as reduce the administrative burden faced by lecturers and the administration. This research contributes to the academic community by providing a practical tool that enhances the efficiency of BKD management. The application reduces administrative overhead, minimizes errors associated with manual processes, and improves the transparency and accessibility of BKD records. Furthermore, this study offers insights into the challenges and best practices in developing digital solutions for academic administrative tasks, potentially serving as a model for similar initiatives in other educational institutions